SOSIALISASI DAN STUDI BANDING ENTREPRENEUR BERBASIS SAWIT PADA PEMBIBITAN SAWIT APKASINDO DI PEKANBARU - R. Rudi Alhempi; Agustin Basriani; Rahmi Zainal; Jusmarni Jusmarni; Resti Riandi; Sri Wahyuni; Dodi Agusra; Sri Mulyana; Nurmansyah Nurmansyah; Marlinda Saputri; Alief Feisal H (Jurnal Pengabdian Kompetitif, 2026)
Palm oil is one of the leading commodities that significantly contributes to the economy of Riau Province. However, many community members and business actors still lack understanding regarding entrepreneurship opportunities in the palm oil sector, particularly in seedling businesses. This community service program aimed to improve participants’ knowledge, insights, and motivation regarding palm oil-based entrepreneurship through socialization and benchmarking activities at the APKASINDO palm oil nursery center in Pekanbaru. The methods used included counseling, interactive discussions, field observations, and benchmarking studies. Participants consisted of palm oil farmers, nursery business actors, APKASINDO administrators, and university students. The results showed an increase in participants' understanding of palm oil nursery business opportunities, business management, superior seed marketing, and agribusiness development strategies. The program also provided direct learning experiences regarding professional nursery management practices. This activity is expected to encourage the emergence of new entrepreneurs in the sustainable and competitive palm oil sector.